2016
DOI: 10.1007/s00038-016-0880-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceived classism and its relation with socioeconomic status, health, health behaviours and perceived inferiority: the Dutch Longitudinal Internet Studies for the Social Sciences (LISS) panel

Abstract: ObjectivesClassism might be the downside of the prevailing ideologies of individual responsibility for success. However, since studies into perceived classism have mainly been qualitative, little is known about its association with socioeconomic status, health, health behaviours and perceived inferiority, especially in more egalitarian countries. This study, therefore, examined the associations of perceived classism with socioeconomic status, health, health behaviours and perceived inferiority.MethodsWe used c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Several international studies suggest that such experiences may be associated with poorer health outcomes. In the United States for example, experiences of poverty and SEP-based stigma have been found to predict various markers of relatively poor mental health, including depressive symptoms, low self-esteem, and feelings of social anxiety and shame (Mickelson and Williams, 2008; Ren et al, 1999; Simons et al, 2017). Further still, one recent study reported that SEP-based discrimination predicts relatively poor sleep quality amongst African Americans (Van Dyke, Vaccarino, Quyyumi and Lewis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several international studies suggest that such experiences may be associated with poorer health outcomes. In the United States for example, experiences of poverty and SEP-based stigma have been found to predict various markers of relatively poor mental health, including depressive symptoms, low self-esteem, and feelings of social anxiety and shame (Mickelson and Williams, 2008; Ren et al, 1999; Simons et al, 2017). Further still, one recent study reported that SEP-based discrimination predicts relatively poor sleep quality amongst African Americans (Van Dyke, Vaccarino, Quyyumi and Lewis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Discrimination has been defined as a structural determinant of health inequalities and people who have suffered experiences of racism, sexism or classism are more likely to have health problems (Borrell et al, 2010;Gil-Gonzalez et al, 2014;Simons, Koster, Groffen, & Bosma, 2016). In the case of women in the context of prostitution, they must face a cumulative vulnerability for being on a smaller scale in the structure of society and gender discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Self-rated health was measured through a single-question: “How would you describe your health, generally speaking?” Scores ranged from 1 ( poor ) to 5 ( excellent ), with higher scores indicating better self-rated health. A single-item measure of self-rated health has been widely used in the literature, has been found to be a unique predictor of mortality (Idler & Benyamini, 1997), and has been associated with perceived classism (Adler et al, 2000; Simons et al, 2017). The mean self-rated health for this sample was 3.63 in a 5-point scale.…”
Section: Methodsmentioning
confidence: 99%
“…Further, classism has been found to be a negative predictor of life satisfaction, GPA (Allan, Garriott, & Keene, 2016), and career self-efficacy (Shin & Lee, 2017). It has also been associated with self-rated health problems and feelings of inferiority in a Dutch sample (Simons, Koster, Groffen, & Bosma, 2017). Whereas support exists in the literature for the deleterious effects of classism on overall functioning, it has mostly focused on college settings, partly due to the lack of measurement tools validated with other populations.…”
mentioning
confidence: 99%